신용평가기능 개선을 위한 과제 - 조성빈 (12006, 2011)
Credit rating agencies(CRAs) are accused of failing to provide accurate and fair credit ratings and hence being responsible for the crisis. This paper tries to add on to the literature on credit rating reform through examining the CRAs in a model where ra